An Unusual Cause of Large Bowel Obstruction in a Patient With Ulcerative Colitis. Issue 7 (20th July 2021) - Moktan, Varun P.; Koop, Andree H.; Olson, Matthew T.; Lewis, Michele D.; Gomez, Victoria; Farraye, Francis A.
ABSTRACT: Endometriosis is a rare cause of large bowel obstruction and has been infrequently reported in patients with inflammatory bowel disease. We present an unusual case of a young woman with ulcerative colitis, who presented with a large bowel obstruction with colonic stricture and peripancreatic mass concerning for malignancy. The evaluation revealed endometriosis, and her large bowel obstruction was successfully managed with leuprolide and colonic stenting.